Description of Measles Epidemiology in the City of Kediri in 2014 – 2017: (Case Study of Data Case Based Measles Surveillance / CBMS at Kediri City Health Office) - Abdul Faqih; Mateus Sakundarno (Universitas STRADA Indonesia, 2019)
Measles is a highly contagious disease caused by viruses and transmitted through coughing and sneezing. Symptoms of measles are high fever, spotting redness of the skin (rash) is accompanied by coughing and / or runny nose and / or conjunctivitis. In 2017 the highest measles incidence in the City of Kediri was the age group less than 15 years, namely 71.6 per 100.000 population. In addition to immunization coverage low in 2016, CBMS achievements in the last four years were also still below target, is a factor that is thought to affect the high incidence of measles in the City of Kediri. This study aims to describe the epidemiology of measles in Kediri City in the year 2014 - 2017. This research is an observational descriptive study. Population at this research is CBMS data in the City of Kediri Health Office in 2014 - 2017.